Perlindungan Seed Phrase dengan Enkripsi Dual-Layer Menggunakan Algoritma AES dan Caesar Cipher - Raihan Akbar Maulana; I Wayan Santiyasa (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
In the digital era, securing sensitive information such as seed phrases are crucial to prevent unauthorized access and potential loss of digital assets. This paper proposes a novel approach for protecting seed phrases using dual-layer encryption with AES algorithm and Caesar cipher. The AES algorithm is utilized to encrypt the seed phrase itself, providing a strong first layer of defense. Additionally, Caesar cipher is employed to encrypt the AES secret key, adding an extra layer of security to the encryption process. By combining these two encryption techniques, the security of the seed phrase is significantly enhanced, as both the phrase and its encryption key are protected. Furthermore, the encrypted seed phrase and key can be securely stored using email as a digital storage medium, enhancing accessibility while maintaining robust security measures.